The Benefits of Empon-Empon and Gembili Bulbs and Testing the Level of Likeability of Processed Products - Dwiyati Pujimulyani; Bayu Kanetro; Sri Winarti (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2023)
Most Indonesian people do not know the benefits of some local food ingredients, namely empon-empon and gembili tubers. Empon-empon contains antioxidants such as polyphenols, while gembili tubers contain inulin. Empon-empon can be processed into an instant powder product which is practical for consumption. Gembili tubers can be processed to be flour and then used it as cookies ingredient. This service activity is in the form of counseling on the benefits of empon-empon and gembili tubers, as well as how to process them. The activity partners are the management of Himatepa and HMPPI within UMBY and UPN